Teacher’s Readiness In Implementing Merdeka Curriculum At Bina Qurani City School, Bogor City - Maulana Hidayat, Firman (Sean Institute, 2024)
The Merdeka Curriculum introduced allows for more flexible teaching methods and is tailored to the needs of students. The implementation of Merdeka Curriculum at Bina Qurani Junior High School shows that this school started implementing this curriculum for grades seven and eight in the 2022/2023 school year. Teachers are given training to ensure readiness in implementing the curriculum. However, in the implementation in grade eight, there was no prior training for teachers, so they had to take the initiative to share their experiences. Teachers' readiness to implement Merdeka Curriculum is important, both in terms of the availability of teaching materials and teaching readiness according to the implemented curriculum. Data collection in this study uses several techniques to obtain information. And the data collection techniques used in this research are interviews, observation, and documentation. As well as using triangulation techniques between interviews and observations to assess teacher readiness in implementing the Merdeka Curriculum at Bina Qurani City Junior High School. The results of interviews and observations show that in the aspect of lesson planning, all teachers have fulfilled the readiness and availability requirements, including the formulation of learning objectives (TP), setting the flow of learning objectives (ATP), and preparing teaching modules. This is in accordance with the learning and assessment guidelines for early childhood education, primary and secondary education. In the implementation of learning, teachers follow several stages, including introduction, core and closing activities that include apperception, motivation, communication of learning objectives, mastery of materials, provision of reading materials, facilitation, concrete examples, as well as learning evaluation and time management.In the aspect of learning assessment, all teachers observed also fulfilled the readiness and availability requirements, covering initial, formative and summative assessments. Initial assessment explores student readiness at the beginning of learning, formative assessment is conducted at the end of each chapter, and summative assessment is conducted at the end of the semester online. The results of technique triangulation showed reliable data. The researcher also triangulated sources by comparing interview responses from the principal, homeroom teacher, English teacher, Physical Education teacher, and Islamic Religious Education teacher. The results show consistency in the formulation of learning objectives and learning assessment, so the data can be declared valid.